RIVER SAND AND SEA SAND MINING INDUSTRIES IN SRI LANKA - M. Darshana & S. P. R. Samanthika (International Journal of Research Science and Management, 2017)
This report has been discussed sea sand and river sand mining in Sri Lanka. To find out the consequences of the present situation regarding sand market and problems arise due to high demand. Currently, Sri lanka is facing sever environmental problems due to sand mining such as river bank erosion, saline water intrusion, destroying of coastal, loss of land and loss of live hood due to flooding. Beside all there are production related problems and marketing problems also can be seen in this industry. This paper has suggested some long term and shortterm solutions for these issues